Teacher Suggestion Feedback Facilitates Creativity of Students in STEAM Education - Shen, Sha; Wang, Saidi; Qi, Yun; Wang, Yanli; Yan, Xiangdong (Frontiers in Psychology, 2021)
This study examined the influence of the formative feedback types of teachers on creativity in Science, Technology, Engineering, Art, Mathematics (STEAM) education. Participants were 90 undergraduate students who were randomly assigned to the teacher opinions feedback group, the teacher suggestion feedback group, or the non-feedback group, and took part in three courses of STEAM education of 3D-printing technology. Before and after each course, they were asked to fill out the Eugene Creativity Test. The results showed that compare with the teacher opinions feedback group and the non-feedback group, the participants in the teacher suggestion feedback group showed a higher score on the creativity scale. This suggests that the teacher suggestion feedback can be useful for improving the creativity in STEAM education.